Conformal Band-Notch UWB Monopole Antenna on Finite Cylindrical Substrates - Ahmed, E. S. (Engineering, Technology & Applied Science Research, 2013)
A microstrip-fed new UWB monopole antenna with a band-notch characteristic mounted on the finite cylindrical surface is presented. The proposed antenna consists of a rectangular metal radiation patch fed by a 50 ohm microstrip line and a rectangular ground plane. To achieve ultra-wideband, three modifications are introduced. The first one is to blend the upper and lower corners of the radiating plates. The second one is to remove a circular section from the radiating metal. The third one is to blend the upper corners of the ground plane. The antenna is designed on a substrate with dielectric constant εr=3 and 1.6 mm height. The proposed antenna is conformed on finite cylindrical substrates of radiuses 4, 5 and 6 cm. The cylindrical structures were simulated through CST microwave studio finite element package. The simulation results, obtained via CST package on the return losses, VSWR and radiation pattern of the antenna are presented. For both planar and conformal antennas, results show that the impedance bandwidth of the designed antenna is from 2-18 GHz with a return loss less than -10 dB (VSWR<2) and a band rejection of 5-6 GHz for wireless LAN (WLAN), that includes the band 5.15-5.825 GHz limited by IEEE 802.11.a and HIPERLAN/2 with return loss greater than -10dB. The proposed simple shaped conformal antenna provides a good radiation pattern and gain between 3.84 and 5.96 dBi over the entire frequency band excluding the rejected band.